2022
DOI: 10.5937/menhottur2202025s
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of the usefulness of online reviews in the tourist offer selection

Abstract: The dynamics of the development of tourism sector is reflected, among other things, in the fact that an increasing number of tourists choose an offer based on online reviews. Although it is true that due to the intensive development of communication via the Internet, online reviews are one of the dominant sources of information, their level of perceived usefulness may differ. The aim of the research is to examine the extent to which textual comments, photos and ratings of tourist offers determine the usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In a similar survey in conducted Croatia (Cerjak, Tomić, 2014;Sofronijević & Kocić, 2022) the results have shown that only 18.3% of surveyed businesses sell their own products over the Internet. According to respondents, the main reason for not using Internet sales is the lack of interest of customers for this way of shopping.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In a similar survey in conducted Croatia (Cerjak, Tomić, 2014;Sofronijević & Kocić, 2022) the results have shown that only 18.3% of surveyed businesses sell their own products over the Internet. According to respondents, the main reason for not using Internet sales is the lack of interest of customers for this way of shopping.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Various social platforms provide users with the ability to share and promote information important for making travel decisions (Filipović et al, 2023). These posts can affect tourists' choice (Fatanti & Suiadnia, 2015;Sofronijević & Kocić, 2022), but in the same time be a very abundant data source for the scientific public when analyzing contemporary tourism trends (Zeng & Gerritsen, 2014). The Instagram platform, which is based predominantly on images, is particularly significant and aligned with the tourism industry due to "the particularly visual nature of tourism content" (Smith, 2019, p. 2).…”
Section: Introductionmentioning
confidence: 99%